Evaluation of the Greenship GBCI Implementation in the Appropriate Land Use Category for the New Building of Poltekkes Riau Tower - Puja Kusumah, Dadang; I Nengah Tela; Haryani (Institut Teknologi dan Bisnis Ahmad Dahlan, 2025)
Implementing the green building concept is a strategic solution to support sustainable development, particularly in the construction sector, which significantly contributes to environmental degradation. In Indonesia, the Green Building Council Indonesia (GBCI) has established the Greenship rating tool as a standard for green buildings, including the Land Use Efficiency category. Menara Poltekkes Riau was selected as the research object because it is a new building aligned with sustainable development principles as stipulated in the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/MENKES/550/2024. This study aims to evaluate the application of the Land Use Efficiency category, measure the level of achievement, and provide recommendations for improvement. The research employs a mixed-method approach (quantitative and qualitative), with data collected through field observations and an As-built Drawing document study. The evaluation results indicate that Menara Poltekkes Riau achieved 5 out of 17 points or 5% of the total points in the Land Use Efficiency category. The criteria achieved include Basic Green Area (ASD-P) Benchmark 1A, Site Selection (ASD-1) Benchmark 1A, Community Accessibility (ASD-2) Benchmark 1, Public Transportation (ASD-3) Benchmark 1A, and Microclimate (ASD-6) Benchmarks 1A and 2. However, other criteria have not been met, including optimizing green areas, vegetation, transportation facilities, accessibility, and stormwater runoff management. This study emphasizes the importance of improving these aspects to enhance the application of the green building concept at Menara Poltekkes Riau.